Tobacco use and practice of physical activity in a melillense population - San Román-Mata, S.; Fernández-Revelles, A.; Valdivia-del Moral, P.; Martínez-Martínez, A.; Castro-Sánchez, M. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2019)
Introduction: Tobacco use is considered a risk factor in the development of multiple pathologies at the pulmonary and cardio-vascular levels, among others. In this sense, the practice of physical activity is considered a factor of protection. Objective: To describe the socio-demographic variables and quality of life in terms of tobacco use and the practice of physical activity in a Melillense population. Material and Method: Research work with quantitative design, descriptive and cross section of a sample of residents in Melilla, about tobacco use and the practice of physical activity. Results: More than three-quarters of the participants said no smoking and three out of ten subjects did not perform any physical activity. Conclusions: We must continue working to strengthen healthy behaviors in the population, in relation to the consumption of harmful substances and the practice of physical activity.